(untitled) (Emancipação, 2026)
The article aims to offer legal and operational guidelines for the use of the non-criminal prosecution agreement as an instrument of victim appreciation and integration of criminal relief with the restorative practices. Based on the literature review, reflections were made on the treatment of the victim in the context of the Brazilian legal system, its relationship with restorative justice and its role in concluding the non-criminal prosecution agreement. Furthermore, through interviews and a questionnaire, it as analyzed how the non-criminal prosecution agreement can be used as means of promoting victims’ rights and restorative justice. As a result, the dialogue flows between restorative practices and the non-criminal prosecution agreement were organized, concluding that this dialogue was viable and relevant considering the policies of encouraging self-composition and promoting resolute action in the Public Prosecutor’s Office and judicial policy of valuing the victim and restorative justice.